INDUCTION OF SOMATIC MUTATION IN CHRYSANTHEMUM CULTIVAR LOCAL GOLDEN - UDAY H. PATIL, SACHIN D. PARHE SANTOSH C. PULATE, (The Bioscan, 2015)
The rooted sucker of chrysanthemum cultivar “Local Golden” was treated with 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 Krad of gamma rays. Each treatment consisted of 25 suckers. The data were recorded on vegetative and flower traits i.e. survival percent, days for sprouting, plant height, internodal distance, number of branches per plant, number of sucker per plant, total crop duration. Flowering behavior (days to bud initiation, days to full bloom, diameter of flower, number of ray florets per flower, number of flower per plant, colour of ray and disc florets). There were no leaf and floral abnormalities in treated plants. LD50 was determined in between 2.5 and 3.0 Krad dose of gamma rays. There was no significant difference in colour of florets of treated and control plants. Chimera in ray florets of flower was observed in one plant after 1.5 Krad treatments. The original shape of ray florets was flat with small tube at the base whereas in case of tubular mutant, shape at tip was spoon type and basal portion showed pipe or tube like appearance.